2009
DOI: 10.2106/jbjs.h.00902
|View full text |Cite
|
Sign up to set email alerts
|

Computed Tomographic Angiography in Proximal Femoral Focal Deficiency

Abstract: Computed tomographic-angiographic reconstruction can be used to depict the spatial configuration of the pseudarthrosis and the vascular pattern of the extremity in patients with proximal femoral focal deficiency. We found distinct vascular changes in the majority of the involved thighs, but there were no typical changes related to the Pappas classification. Because we found atypical vascular patterns in two patients, evaluation of the vessels with use of various diagnostic methods is recommended in patients wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 8 publications
3
17
0
Order By: Relevance
“…Pirani et al 11 reported most muscles around the hip joint to be present, but hypoplastic, from MRI studies. Chomiak et al 12 performed CT angiographic studies and reported that many of their PFFD patients had external iliac, femoral and deep femoral arteries of reduced length and diameter. The deep femoral artery arose more proximally than normal.…”
Section: Discussionmentioning
confidence: 99%
“…Pirani et al 11 reported most muscles around the hip joint to be present, but hypoplastic, from MRI studies. Chomiak et al 12 performed CT angiographic studies and reported that many of their PFFD patients had external iliac, femoral and deep femoral arteries of reduced length and diameter. The deep femoral artery arose more proximally than normal.…”
Section: Discussionmentioning
confidence: 99%
“…The critical time for connection between the femoral artery and the sciatic (ischiadic) artery in the femoral region of the lower extremity is estimated to occur between the 12 mm and 14 mm stages of embryonic development (approximately embryonic week six) (Chomiak, Horak, Masek, Frydrychova, & Dungl, 2009;Senior, 1919aSenior, , 1919b. The critical time for arterial changes of the more distal part of the lower extremity in the tibial and fibular regions is estimated to occur between the 19 mm and 22 mm stages of embryonic development (approximately week seven) (Hootnick et al, 1980b;Levinsohn et al, 1991;Senior, 1919a).…”
Section: Vascular Injury As a Mechanism For Embryonic Bone Loss Andmentioning
confidence: 99%
“…Congenital arterial anomalies have been independently reported as associated with an asymmetric, noncontiguous pattern of congenital femoral (Chomiak et al, 2009), fibular (Bedoya et al, 2015;Hootnick et al, 1980b;Huda et al, 2014), and midline metatarsal (Hootnick, 2014;Hootnick, Packard, & Levinsohn, 1983;Hootnick et al, 1980a) long bone deficiencies. The skeletal pathologies are manifested by dysmorphic bony patterns, which, interestingly, correspond closely to the embryonic arterial in-growth pattern of the late embryonic limb, ascribed to Senior (Senior, 1919a(Senior, , 1919b(Senior, , 1985.…”
Section: Vascular Injury As a Mechanism For Embryonic Bone Loss Andmentioning
confidence: 99%
“…This classification system separates PFFD on the basis of the presence of anatomic features of the femoral head, acetabulum, and femoral segment. 17,18,24 According to the radiographic appearance on plain X-ray, the Aiken classification delineated PFFD into four types (A–D). Type A presents as a short femur with a femoral head and acetabulum; there is a possibility of subtrochanteric and pseudoarthrosis.…”
Section: Proximal Femoral Focal Deficiencymentioning
confidence: 99%
“…The most severe situation is type D, where the femoral head and acetabulum is missing, and the femur is short and deformed. 17,18,24 Other classifications were devised with more groupings or with the aid of advanced diagnostic methods. For example, Amstutz categorized PFFD into five types by dividing type A of the Aiken classification into two subgroups on the basis of the presence of subtrochanteric pseudoarthrosis and coxa vara.…”
Section: Proximal Femoral Focal Deficiencymentioning
confidence: 99%